2021
DOI: 10.2196/21728
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Self-management Program (SPACE for COPD) for Individuals Hospitalized With an Acute Exacerbation of Chronic Obstructive Pulmonary Disease: Nonrandomized Feasibility Trial of Acceptability

Abstract: Background Hospital admissions due to the acute exacerbation of chronic obstructive pulmonary disease (AECOPD) are costly for individuals and health services. Pulmonary rehabilitation (PR) is known to reduce hospital readmissions when delivered after hospitalization, but the uptake and completion of PR following hospitalization remains poor (<10% of those eligible in the UK audit data). A web-based platform of the SPACE (Self-management Program of Activity Coping and Education) for COPD (chronic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Predominate reasons for exclusion reported were not being web literate (69%), unwilling (15%) or had comorbidities precluding involvement (12%). 13 Our study findings that recruiting patients with COPD during hospitalisation can be difficult appear to be supported by the literature.…”
Section: Discussionsupporting
confidence: 84%
“…Predominate reasons for exclusion reported were not being web literate (69%), unwilling (15%) or had comorbidities precluding involvement (12%). 13 Our study findings that recruiting patients with COPD during hospitalisation can be difficult appear to be supported by the literature.…”
Section: Discussionsupporting
confidence: 84%
“…A significant increase in measuring learning outcomes has occurred in the last decade with 6 of the 13 studies evaluating gain of skills, knowledge, and attitudes. In adults, technology-enabled patient education showed an increased disease specific knowledge [12,21] and inhaler technique improved [13]. The perception of coping with the condition also increased [12].…”
Section: Gain Of Skills and Knowledgementioning
confidence: 97%
“…For all studies that measured patient satisfaction, technology-enabled patient education was a positive experience by the majority of participants. The majority of participants would recommend the technology-enabled patient education to peers, finding the webbased and application-based education kept them motivated, was easy to use, and was relevant and perceived their knowledge and skills to have improved [5,6,9,12,[14][15][16]21,23]. Participants also found that the technology solution meant the information was always readily available and not able to be misplaced, and this was very helpful [6].…”
Section: User Satisfaction With Technology-enabled Patient Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Infarinato and colleagues developed a scale based on the Technology Acceptance Model (TAM [41,42]) and were able to demonstrate that patients' intention to use their remote rehabilitation program depended on their perceived usefulness and ease of use of the program [43]. Houchen-Wolloff and colleagues leveraged qualitative methods to understand patient perceptions of their web-based self-management program [44]. Through interviews, they discovered that those who felt more comfortable with a computer were more willing to engage with the intervention and felt a stronger sense of motivation.…”
Section: Involving Stakeholdersmentioning
confidence: 99%